Quest for a sustainable legal framework for the protection of women’s right to dignity in Nigeria: Lessons from India and South Africa / Aloysius Ndubuisi Ojilere - Aloysius, Ndubuisi Ojilere (2015)

(untitled)
Nigeria and India are former British colonies. Both countries have similar constitutional framework on fundamental rights and directive principles of state policy. South Africa, with Dutch and British colonial legacies, on the other hand, is arguably, the most advanced constitutional democracy in Africa, and perhaps, in the world today. Nigeria, India and South Africa are developing countries in the Global South. They all lean strongly towards patriarchal and socio-religious mythology. These three countries belong to the same common law family of mixed legal systems. Legal transplant is, therefore, possible between them. Strategically speaking, Nigeria and India are the largest democracies in Africa and Asia respectively. Statistically, women outnumber men in South Africa while in Nigeria and India they constitute nearly half of the population. These women unfortunately are vulnerable. They suffer similar indignity of rape, marital rape, sexual harassment and other humiliation arising typically from patriarchal mind-sets, beliefs in certain socio-religious mythologies or ancient customary practices including castes, dowry and bride price, widowhood rites and son preference, which diminish the self-worth and dignity of women. On the basis of some of these abuses only, these countries have been derided as dangerous places for women to live in. Nigeria, in particular, is further ridiculed as being “notorious for violating international agreements”. The Nigerian legal framework, comprising constitutional guarantees, law and policy formulations as well as judicial responses, for the protection of the right to dignity of women, has been vigorously criticized for falling short of international law, unsustainable and incapable of supporting the United Nations’ Millennium Development Goal No. 3 on gender equality and empowerment of women. In South Africa, things are however different. The pragmatism of the Constitutional Court and the superior Bill of Rights provisions in the Constitution are legendary. They iv easily rank among the best in the Global South as well as the Global North. India is also forward-looking. With basic legal and policy protection of women’s right to dignity and sexual safety, coupled with judicial independence, creativity and activism in the interpretation of both positive and negative constitutional rights, India, too, is exemplary. It showcases and distinguishes the Indian Supreme Court, alongside the more outstanding Constitutional Court of South Africa, as consequential courts and activist tribunals in the Global South in the 21st Century. This thesis highlights certain abuses of the right to dignity of women in Nigeria, India and South Africa (as mirror of the most African and Asian women). It explores international law, as well as the transformational advances in the legal framework (constitutional, judicial, legislative and policy) governing the protection of women’s right to dignity in India and South Africa, from which valuable lessons may reasonably be applied to bridge the inherent fundamental gaps in the existing Nigerian framework. Finally, it recommends reforms in the quest for a sustainable legal framework for the protection of the right to dignity of women in Nigeria. Incidentally those recommendations may also be useful to other developing common law jurisdictions in similar circumstances. This research is qualitative and doctrinal. It is based purely on library and desktop research including analysis and valuable information from legal provisions, case-law, as well as writings and opinions of eminent scholars and jurists.